Knowledge and perception of nutrition educators on the food guide pyramid a baseline study - Pastores, Grace Aurora F.; Panlasigui, Leonora N. (2002)
This study was conducted to determine knowledge and perception of nutrition educators on the food guide pyramid. Five hundred sixty six nutrition educators participated from the 11 cities and 6 municipalities of the National Capital Region (NCR) served as respondents of the study. Results showed that nutrition educators have fair basic nutrition knowledge but have low knowledge about the food guide pyramid. Correlation analysis revealed that age is inversely correlated, while educational attainment and training on growth monitoring and nutrition education are positively correlated with nutrition knowledge. Training on growth monitoring is significantly related to knowledge on the food guide pyramid. Income was found to be significantly related to perception about the food guide pyramid. Nutrition educators perceive the food guide pyramid to be a useful nutrition education tool despite their low knowledge on its content. Nutrition educators' concept of messages conveyed by the food guide pyramid is about balanced diet, which means eating a variety of foods. Nutrition educators expected a colorful food guide in whatever shape or form. Despite their low knowledge scores on the food guide pyramid, they found it to be attractive in color, shape and layout. Correlation analysis revealed a significant positive relationship between knowledge and perception on the food guide pyramid.
Thesis(M.S. Nutrition)--University of the Philippines, Diliman.
Keywords: Nutritionists -- Philippines -- Manila Metropolitan Area; Nutrition -- Requirements; Food combining